2006
DOI: 10.1143/jjap.45.7108
|View full text |Cite
|
Sign up to set email alerts
|

Trapping Laser Ablated Ca+ Ions in Linear Paul Trap

Abstract: We have investigated the efficiency of ion trapping in a linear Paul trap. First, we measured the dependence of trapping efficiency on dc and rf voltages using a channel electron multiplier for the direct detection of the electric current of the trapped ions. The most efficient dc and rf voltages were 5.0 and 175 V, respectively. Second, we calculated the trapping efficiency using a simulation code and compared it with the experimental results. We determined that the efficiency of ion trapping decreased monoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 15 publications
4
29
0
Order By: Relevance
“…The ion loading efficiency may be improved over that of Ref. [39] by using a cryogenic Ne buffer gas [40] at T ≈ 30 K. Once the ion trap is loaded, the cryostat temperature may be lowered to ∼4 K, resulting in fast cryopumping of the Ne buffer gas by charcoal sorbs [41]. Next, ultracold Yb atoms are collected in a standard MOT (represented by the blue cloud in Fig.…”
Section: Experimental Implementationmentioning
confidence: 99%
“…The ion loading efficiency may be improved over that of Ref. [39] by using a cryogenic Ne buffer gas [40] at T ≈ 30 K. Once the ion trap is loaded, the cryostat temperature may be lowered to ∼4 K, resulting in fast cryopumping of the Ne buffer gas by charcoal sorbs [41]. Next, ultracold Yb atoms are collected in a standard MOT (represented by the blue cloud in Fig.…”
Section: Experimental Implementationmentioning
confidence: 99%
“…We are especially interested in the production of Th + for an investigation of a nuclear optical clock based on the low energy transition to an isomeric state in 229 Th [7]. Previous studies have already reported laser ablation from metals for the loading of ion traps [5,[8][9][10][11][12][13], but typically higher laser pulse energies at infrared wavelengths were used and experiments were carried out only for a small selection of elements. Laser desorption of organic molecules has been studied in conjunction with ion trap mass spectrometry (see for example Refs.…”
Section: Introductionmentioning
confidence: 99%
“…These ions can be loaded into the ion trap in a number of ways. First, as was demonstrated in [55] the plasma itself can short-circuit the trap electrodes causing a sag in the trapping voltages. By the time the voltages recover, low energy ions from the ablation plume have moved into the trap volume and the trap potential recovers around them.…”
Section: Generation Of Molecular Ionsmentioning
confidence: 99%